PELATIHAN ECOPRINT IBU-IBU PKK DESA SIMO KECAMATAN KENDAL KABUPATEN NGAWI - Indra Lila Kusuma; Johny Subarkah; Andrean Wahyu Parawangsa; Leni Elviana; Lisa Ayu Ramadhani; Nendy Akbar Rozaq Rais; Ardyan Firdausi Mustoffa (LPPM ITB AAS Indonesia Surakarta, 2023)
The ecoprint training aims to provide direct benefits to the community in social and economic life and to improve the quality of resources through empowering PKK women in Simo Village, Kendal District, Ngawi Regency by utilizing natural materials in the vicinity of the residence. This activity is expected to be able to solve problems in the partner villages, namely the community's source of income is only dominated by the agricultural sector, the village's natural potential has not been utilized properly, lack of skills in managing village potential, the majority of Simo Village residents are housewives with minimal income. community partnership. This program consists of two activities, namely training on making ecoprints using natural materials in the environment around Simo Village and an explanation via PPT on how to make ecoprints. It is hoped that the partnership program activities can be carried out continuously so that they can become additional livelihoods for the surrounding community because the selling value of ecoprint products is still quite high in the market. Keywords : ecoprints; Income; Natural ingredient; Ngawi